The Application of Natural Phenolic Substances as Antimicrobial Agents in Agriculture and Food Industry - Katarzyna Dembińska; Ambika H. Shinde; Marcela Pejchalová; Agnieszka Richert; Maria Swiontek Brzezinska (Foods)
Natural phenolic substances have emerged as promising alternatives to synthetic antimicrobials in both agriculture and the food industry, where concerns over microbial resistance and chemical residues are rising. This review provides a comprehensive overview of the current literature, highlighting the potential of these compounds as effective antimicrobial agents. A systematic evaluation of in vitro and in vivo studies was conducted, focusing on the efficacy of various phenolic compounds against a range of pathogens. The analysis revealed that natural phenolics not only inhibit microbial growth but also enhance the shelf life and safety of food products and protect crops from disease. Moreover, although laboratory results are promising, the translation of these findings into practical applications requires further investigation. Overall, the evidence supports the potential for natural phenolic substances to serve as integral components in sustainable agriculture and food preservation strategies.